Identifying three different architectural subtypes of mammary ductal carcinoma in situ using multiphoton microscopy. (10th September 2015) - Wu, Yan; Fu, Fangmeng; Lian, Yuane; Nie, Yuting; Zhuo, shuangmu; Wang, Chuan; Chen, Jianxin
Abstract: Ductal carcinoma in situ (DCIS) is often considered as the precursor of invasive breast cancer, and the risk of DCIS progression to IBC has been estimated based on the evaluation of pathological features, among which the architectural subtype is the most common one. In this study, multiphoton microscopy (MPM) is applied to identify three different architectural subtypes of DCIS (solid, cribriform and comedo). It is found that MPM has the capability to visualize the proliferating pattern of tumor cells, the presence of intraluminal necrosis and the morphology of basement membrane, which are all taken into account in subtyping DCIS. In addition, MPM also can be used to quantify the cellular metabolism, for quantitatively identifying tumor staging during tumor progression. This result highlights the potential of MPM as an advanced technique to assess the pathological characters of the breast tumor in real-time and reflect the degree of tumor progression in vivo, by integrating into the intra-fiberoptic ductoscopy or transdermal biopsy needle.